Peran IBI dalam Implementasi Kebijakan PP RI No.33 Tahun 2012 Tentang Pemberian Air Susu Ibu Ekslusif di Kota Bengkulu - Lela Hartini (Poltekkes Kemenkes Jakarta III, 2019)
An indicator of increasing degree of health marked by declining infant mortality (AKB). The risk of AKB could be reduced by as much as 22% with exclusive breast feeding. IBI as the only organization that embraces a midwife in the profession of midwifery and support government program. The purpose of this research is to know the performance of the role Ikatan Bidan Indonesia (IBI) administrators in the implementation of the policies of the PP RI No. 33 2012 about giving breast milk in Bengkulu. Methode of this research is qualitative descriptive observational design by indepth interview on 3 persons Caretaker IBI, Triangulasi with Chairman IBI Province, Kasie Nutrition health services and a member of region parlement. The results are the role of the IBI performance as implementers include motivating, evaluating and coaching to members in the implementation of the policies has still not acted properly. The role of caretaker manager in developing service of midwifery are still lacking regulatory cooperation with the health services as well as related government agencies. While the role of decision makers, educators and health extension officers also did not exist. Suggested for IBI to increase the motivation, coaching and supervision to the midwife, give a reword or formal sanction to Independent Practice midwives